Perbandingan Sistem Merit di Partai Keadilan Sejahtera dan Partai Solidaritas Indonesia - Laga Sugiarto (LPPM Universitas Harapan Bangsa, 2022)
Governance that can serve people optimally decided by quality of its leader, someone who emerge from recruitment, selection and promotion process within political party, that is underpinned of merit system, a system that based on three major principal, namely, virtue, social skill and capability. merit system has been implemented optimally in difference level by both Prosperous Justice Party (PKS) and Indonesian Solidarity Party (PSI). meanwhile, this research use empirical juridical method. in conclusion, this research can contribute to all parpol and goverment regarding with reform of political party management in the future that must be based on merit system.